Superior Sclera Versus Temporal Corneal on Steep Axis Incision to Correct Pre-Existing Corneal Astigmatism Less Than 1.5 D - KavitaBhatnagar; Khanna Aman; Pujari Sudeep (Journal of Ophthalmic Science, 2015)
Purpose: Cataract is the leading cause of blindness worldwide. Even in an uneventful cataract surgery, surgically induced astigmatism remains the major hurdle in attaining good unaided visual acuity post surgery. If pre-existing corneal astigmatism is not corrected at the time of surgery, it will result in more postoperative astigmatism; therefore, it is important to correct pre-existing corneal astigmatism. Material & Methods In this prospective study, 100 eyes of 100 age and sex matched patient’s with comparable preoperative astigmatism and visual acuity were divided in two groups according to pre operative corneal astigmatism. SIG (superior scleral incision group) included 50 eyes with steeper vertical axis and TIG (temporal corneal incision group) included 50 eyes with steeper horizontal axis. SIG and TIG were subjected to superior scleral tunnel and temporal corneal tunnel incisions respectively. Corneal astigmatism was measured preoperatively and at 1, 2 and 6 weeks postoperatively. Results: The mean postoperative astigmatism in SIG and TIG after 6 weeks was 0.545 ± 0.51D and 0.59 ± 0.48 D in comparison to preoperative astigmatism of 1.105 ± 0.54 D and 1.120 ± 0.49 D respectively. The difference was statistically significant in both the groups with P< 0.001 for both groups. The difference in surgically induced astigmatism between the two groups was not significant at any point of time after surgery (p>0.05). Conclusion: Incision site on steeper axis helps in reduction of pre-existing corneal astigmatism in cataract surgery. Both superior scleral and temporal corneal incisions help in neutralization of approx. 0.4-0.7 D of astigmatism.
Keywords: Superior scleral incision